2013
DOI: 10.3354/dao02571
|View full text |Cite
|
Sign up to set email alerts
|

Self-limiting outbreak of crayfish plague in an Austropotamobius pallipes population of a river basin in the Abruzzi region (central Italy)

Abstract: Crayfish plague, caused by the oomycete Aphanomyces astaci, is a serious disease of European freshwater crayfish and has eliminated entire populations in several European countries. In September 2011, mortality was observed among the Austropotamobius pallipes population of a river basin in the Abruzzi region (central Italy), and A. astaci DNA was detected by PCR in dead crayfish. A systematic survey was carried out to evaluate the spread and the effects of the plague in the river basin. The source of the outbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…(i) It is known that crayfish density can act on the quantity of spore production during an outbreak (Caprioli et al, 2013). If so, we could expect more spore production in areas of high density and a quick spread of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) It is known that crayfish density can act on the quantity of spore production during an outbreak (Caprioli et al, 2013). If so, we could expect more spore production in areas of high density and a quick spread of infection.…”
Section: Discussionmentioning
confidence: 99%
“…When plague occurs in a European crayfish population, the population is generally eliminated within short periods of time (Kozubíková et al, 2008;OIE, 2009) although a few cases of chronic infections have been recently reported for indigenous European crayfish species (Caprioli et al, 2013;Kušar et al, 2013;Viljamaa-Dirks et al, 2013). In some cases, the presence of a pond or dam may limit the upstream spread of disease (Kozubíková-Balcarova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Populations isolated due to fragmentation might have an advantage, being less susceptible to the expansion of invasive species and diseases (Caprioli et al, 2013;Kušar et al, 2013). For instance, two of the most representative invasive crayfish species in Europe, the spiny-cheek crayfish, Orconectes limosus (Rafinesque, 1817), and the red swamp crayfish, Procambarus clarkii (Girard, 1852), are adapted for lowland rivers (Holdich et al, 2006) and supposedly unable to colonize mountain streams (Petrusek et al, 2006).…”
Section: Perspectives On Crayfish Conservationmentioning
confidence: 99%
“…In general, this disease has a bad reputation, but some A. astaci strains seem to show signs of avirulence (Jussila et al, 2011a;Makkonen, 2013). Certain strains of this parasite have likely adapted to their fairly recent European hosts, as the As-genotype is currently causing highly variable mortalities among native European crayfish both in laboratory experiments and among wild populations (Jussila et al, 2011Kokko et al, 2012;Svoboda et al, 2012;Caprioli et al, 2013;Kušar et al, 2013). So far, however, the evidence of virulence differences and potential evolution among PsI-genotype, or other more recently introduced A. astaci genotypes, has been lacking.…”
Section: Introductionmentioning
confidence: 99%